2013
DOI: 10.1590/s0034-89102013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Inadequação do consumo de nutrientes entre adolescentes brasileiros

Abstract: OBJECTIVE: to assess energy and nutrient consumption and the prevalence of inadequate micronutrient intake among Brazilian adolescents. METHODS:A random sample composed of 6,797 adolescents (49.7% girls), between 10 and 18 years old, was evaluated in the fi rst National Dietary Survey, part of the Household Budget Survey carried out in [2008][2009]. Expansion factors, sample complexity design and correction of intraindividual variability were considered. The prevalence of inadequate micronutrient intake was ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1
22

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 19 publications
7
32
1
22
Order By: Relevance
“…In this study, as reported in other studies conducted in Brazil [12,38], we observed inadequate vitamin C intake (below recommended levels) in a large proportion of adolescents, possibly reflecting the insufficient consumption of fresh fruits and vegetables characteristic of Brazilian adolescents [36]. According to the Household Budget Survey 2008-2009 [36], which was developed at a national scale, the recommended daily intake of fruit and vegetables of 400 g [39] was not achieved even in the 90th percentile of the population of young Brazilians.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In this study, as reported in other studies conducted in Brazil [12,38], we observed inadequate vitamin C intake (below recommended levels) in a large proportion of adolescents, possibly reflecting the insufficient consumption of fresh fruits and vegetables characteristic of Brazilian adolescents [36]. According to the Household Budget Survey 2008-2009 [36], which was developed at a national scale, the recommended daily intake of fruit and vegetables of 400 g [39] was not achieved even in the 90th percentile of the population of young Brazilians.…”
Section: Discussionsupporting
confidence: 85%
“…However, among those aged 14-19 years, the prevalence of inadequate iron intake was similar to that observed in boys and girls in southeastern Brazil (6.3 and 20.8%, respectively) [36] and across Brazil (11.8 and 25.0%, respectively) [12]. The higher prevalence of inadequate iron intake observed in adolescents between 14 and 19 years is particularly worrying because it increases the risk of developing iron deficiency anemia in a period of life during which the vulnerability to the illness is naturally higher due to the significant increase in daily iron requirements because of rapid growth and muscle mass increases in boys and the onset of the menstrual cycle in girls [37].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations